Reactive coordinated optimal operation of distributed wind generation - Xiang, Yue; Zhou, Lili; Huang, Yuan; Zhang, Xin; Liu, Youbo; Liu, Junyong (Elsevier, 2020)
Large-scale distributed wind generation (DWG) integration brings new challenges to the optimal operation of the distribution network. The reactive supports from wind turbines (WTs) and reactive power resources can improve both the operation economy and renewable energy consumption. In this paper, a multi-period reactive coordinated optimal operation model for DWG in the distribution network is established. The active-reactive power coordination characteristics of two typical types of WTs are considered and the operating strategy of reactive power resources is integrated in the model. The second-order cone programming (SOCP) is developed to transform the original nonlinear power flow model into a linear and convex model, which would significantly improve the power flow calculation efficiency for DWG penetrated distribution network. The simulation results show that the integration of reactive power resources can further promote the consumption of DWG and improve the operating profits of the distribution network.
Keywords: Distributed wind generation; Optimal operation; Active-reactive power coordination; Reactive power resources; Economic benefits